Performace Appraisal: A Tool to Harmonise Fair Promotional Practices in the Organisation - Jain, Sapna (Journal of Commerce and Trade, 2019)
There is a deep throat cut competition in the present day scenario no matter that anyone can be hurt but success and ultimate win is the main priority in the organizations. To curb these situations and to restore the fading harmony in the organisatinal arena, performance appraisal is a good technique to deal. Performance appraisal establishes the fair promotional practices in the organization. It gives motivation to less active personnel as well as boosts the carrier of active personal along with work satisfaction. A particular technique may benefit one organisation, but prove to be completely catastrophic for the other. Thus, a person dealing in the management of human resources and allotted with the task of evaluating employees must keep in mind that he cannot follow what others are doing. Rather, he is required to study various aspects in relation to his organisation, in order to decide the performance evaluation technique best suited for his organisation. Thus, it is imperative for all organisations to see a complete picture through the holistic concept of performance management, rather than sticking to the single element of performance appraisal. Studying the concept of performance appraisal in detail is still of high importance, but in order to reap its benefits, it must be correctly applied and used in the larger process of performance management. Classification-JEL : L 20, M 10, O 15.